An Elastic Triboelectric Nanogenerator for Harvesting Random Mechanical Energy with Multiple Working Modes. Issue 7 (1st April 2019) - Chen, Yuliang; Zhang, Ying; Zhan, Taotao; Lin, Zhiming; Zhang, Steven L.; Zou, Haiyang; Zhang, Guobin; Zou, Chongwen; Wang, Zhong Lin
Abstract: Because of the shortage of fossil energy and the rapid development of Internet of things nowadays, renewable and clean energy is becoming valuable and necessary. One renewable energy source, triboelectric nanogenerators (TENGs), has been proved to effectively harvest energy from vibration, walking, and even sphygmus. TENGs based on contact–separation mode are foremost and fundamental, and the input stimuli for TENGs are strictly limited by constant amplitude and uniaxial direction of motion, which limits many practical applications. Therefore, it is extremely meaningful to develop a kind of TENG to collect random energy, which ubiquitously exists in the ambient environment. Here, an elastic rubber is placed inside the structure of an elastic TENG (E‐TENG). With this novel structure, the output signals of the TENG are almost independent of the amplitude of the external stimuli due to the elasticity of rubber. Moreover, the E‐TENG shows good performance on angle detection without the limitation of the direction of stimuli. It is believed that the E‐TENG will contribute to developing next‐generation flexible TENGs and self‐powered sensors in the future. Abstract : A novel elastic triboelectric nanogenerator (E‐TENG) is presented in this work by introducing elastic triboelectric layer between two electrodes. Due to the elasticity of the E‐TENG, multiple working modes, i.e., single contacting, dual contacting, and rotation modes can be utilized to collect random mechanical energy rather than the single mode in traditional rigid TENGs.